QRICH1 Suppresses Glioma Progression by Inducing ER Stress and Activating the PERK ‐ ATF4 ‐ CHOP Pathway - Yunjiang Wang; Min Xu; Zhenglou Chen; Xuqi Huo; Ya Xue; Xiang Ji; Yang Shen; Hongsheng Wang (Cancer Medicine, 2026)
ABSTRACT Background ER stress (ERS) influences tumor behavior through the unfolded protein response (UPR), yet its role in glioma is not fully defined. This study investigated the function of the ERS‐related regulator QRICH1 in glioma progression. Methods Public databases (TCGA and GTEx) were used to evaluate QRICH1 expression, survival, and prognostic significance in glioma. Lentiviral QRICH1 overexpression or knockdown was established in U87 and U251 cells, followed by functional and mechanistic assays. A subcutaneous xenograft model, histological analyses, and immunohistochemistry were performed to validate the biological function of QRICH1 in vivo. Results QRICH1 was markedly upregulated in glioma and associated with better patient survival. QRICH1 overexpression suppressed glioma proliferation, migration, and invasion while promoting apoptosis, whereas silencing QRICH1 enhanced malignancy. Mechanistically, QRICH1 activated the PERK‐ATF4‐CHOP pathway, increased caspase‐12 cleavage, and strengthened ERS‐induced apoptosis. In vivo, QRICH1 overexpression reduced tumor size and increased apoptotic markers. Conclusion QRICH1 shifts QRICH1 shifts the UPR toward its pro‐apoptotic branch, thereby inhibiting glioma progression, and represents a promising prognostic biomarker and therapeutic target.